Las organizaciones indígenas y campesinas frente al conflicto armado en el norte del Cauca - Moreno Quintero, Renata (Sociedad y Economía, 2008)
This work compare the ways in which the armed conflict affected the indigenous and peasant organizations at north of Cauca in Colombia, and how these organizations reacted in face of the conflict. Explaining why the indigenous organization can resist actively to the armed actors and not the peasant organization is intended.